Survey on implementation of internal Shariah compliance function in Malaysian Islamic banks and takaful companies - Hassan, Rusni; Arifin, Mahamad; Othman, Ahmad Azam; Mohd Napiah, Mohammad Deen; Omar, Muhammad Naim; Yusoff, Adnan; Khatimin, Nuraini; Zaharim, Azami (2013)
The Central Bank of Malaysia has issued Shariah Governance Framework for Islamic Financial Institutions (hereinafter referred to as “SGF”) which was effective starting from January 2011 brought a new dimension and evolution phase in Malaysian Islamic Banking. The issuance of SGF shows the commitment of regulator in enhancing Shariah governance of Malaysian Islamic financial institutions. One of the requirements stipulated in SGF is the requirement for Islamic Financial Institution (hereinafter referred to as “IFI”) to have a robust Shariah compliance function which encompasses ShariahSecretariate, Shariah Review and Shariah Audit, Shariah Risk Management and Shariah Research functions. This study is intended to examine the approaches conducted by the Malaysian Islamic banks in implementing those functions. The finding of this study contributes towards establishing the effective mechanism in implementing Shariah Compliance function which in return beneficial to the industry